Description of Mathematical Reasoning Ability on Vocational School Students in Square Root Material - Hijriani, Lailin; Susiswo, Susiswo (Universitas Tanjungpura, 2021)
The aim of this study is to describe the mathematical reasoning ability of students at TSM major (Motorcycle Engineering) Darul Karomah Singosari on square root material. This study applies descriptive qualitative approach, data was collected using test instrument that has been tested on three research subjects, and analyzed using qualitative descriptive technique. The results show that low- ability (Kemampuan Rendah) subject is the student with less mathematical reasoning ability because the subject has not been able to solve the five existing indicators of mathematical reasoning, middle- ability (Kemampuan Sedang) subject include student with moderate mathematical reasoning ability (although the subject has not fulfilled the five indicators of mathematical reasoning requirements), this can be seen from his effort to make a mathematical assumption even though the conjecture made was not correct, and high- ability (Kemampuan Tinggi) subject refers to the student with high mathematical reasoning ability because he can fulfill two of the five indicators of mathematical reasoning.